Geographical imagination and intra-Asia hierarchy between Filipinos and South Korean in the Philippines - Kim, Dohye (2016)
Dwindling economic opportunities in South Korea after the financial crisis of 1997 spurred forced retirement, with the Philippines emerging as a viable destination for relatively young South Korean retirees. Relations between these retirees and Filipinos have been influenced by the colonial-era system of racial hierarchy, resulting in intra-Asian hierarchies held by both groups. Shedding light on racial relations between postcolonial peoples, this article shows how South Korean retirees? feelings of economic superiority and communal exclusiveness are challenged by the sociocultural advancement of Filipino middle classes. Among South Korean retirees in the Philippines, the imaginary distance between the two countries has widened.
Includes bibliographical references (pages 260-264).
Keywords: Koreans; Koreans -- Migrations; Retirement in foreign countries